The Dual Role of Anxiety in Crisis Response: Emotional Intensification and Prosocial Behavior During the COVID-19 Pandemic - Soohee Kim (Psychiatry International)
The COVID-19 pandemic has profoundly impacted mental health, intensifying negative emotions and challenging collective psychological resilience. This study examines the complex psychological interplay between social media engagement, emotional responses, and behavioral outcomes during crises. Using an online survey (N = 500) conducted during the COVID-19 pandemic, the findings reveal that heightened social media use for social interaction is associated with amplified emotional responses—particularly anxiety, anger, and sadness. Among these, anxiety demonstrated a dual role, acting as both a psychological stressor and a motivator for cooperative and prosocial behaviors, such as supporting government policies, volunteering, and donating. In contrast, anger and sadness were not associated with similar behavioral outcomes. These findings highlight the nuanced psychological impact of anxiety during crises, emphasizing its potential to drive adaptive responses amidst heightened emotional distress. This study contributes to a deeper understanding of how emotional and psychological processes, particularly anxiety, influence public behavior during crises, providing insights for mental health interventions and policy strategies.